Migration governance in Pakistan: institutional challenges and data gaps - Cheema, Abdur Rehman; Rafique, N.; Abbas, F. (SAGE Publications, 2025)
Recent estimations indicate that Pakistan is currently host to approximately 3.28 million migrants, comprising roughly 1.5 percent of the nation’s total population. While Pakistan possesses an extensive national registration database, the National Database and Registration Authority, encompassing both citizens and individuals of Pakistani origin, it is noteworthy that the country lacks a comprehensive migration-sensitive infrastructure. Consequently, there exists a pressing need for in-depth analytical approaches to elucidate the complexities of migration governance and data management within the Pakistani context. Despite the undeniable significance of migration in driving macroeconomic and socioeconomic development within Pakistan, this sector remains notably marginalized in terms of policy prioritization. At present, Pakistan lacks a dedicated migration policy, a centralized coordinating body responsible for managing migration-related data, and a cohesive framework for analytical or advisory efforts regarding the collection and validation of migration data across diverse stakeholders. Consequently, Pakistan’s approach to migration governance is characterized by fragmentation, with numerous government entities engaged in the handling and reporting of migration data and service provision. In light of these circumstances, this country report serves as a diagnostic tool, shedding light on salient governance, and data-related challenges. Its overarching objective is to advocate for the elevation of migration governance to a prominent position on Pakistan’s policy agenda, thereby addressing the pressing issues outlined herein.